Interior Design as a tool for dementia care Experiences and guidelines for the Therapeutic Habitat Model - Silvia Maria, Gramegna (Design International, 2021)
This book investigates the role of interior design in the enhancement of the effectiveness of Non-Pharmacological therapies for Alzheimer's disease care. The author presents the conceptual model for an environmental system called "Therapeutic Habitat", meant as a system of environmental interventions, based on tangible and intangible aspects, products and furniture, objects and services. Its aim is to enhance the well-being of people with dementia and stimulate recognition and interaction with the surrounding environment.